"Kail sejengkal janganlah menduga dalam lautan": Mengapa psikologi perlu lebih daripada studi empiris - Himawan, Karel Karsten (Jurnal Psikologi Ulayat: Indonesian Journal of Indigenous Psychology, 2020)
Most studies in psychology are built on the evidence-based paradigm, which heavily relies on the objectivity (positivism) as well as integrity and competency of the researchers (constructivism) to interpret the reality. Such a paradigm is often implemented in a reductionistic manner, where all studies in psychology have to employ analysis of primary data. This reflects what currently occurs in Indonesia where most scientific outlets in psychology seem to put much interest on manuscripts that report quantitative and/or qualitative study. In this editorial note, I introduce various possible alternative methods to justify the truth and utility values apart from empirical analysis. This note also informs various practical strategies of the journal to accommodate publication of peer-reviewed, non-empirical work for rapid and accurate dissemination of new knowledge in the field of Indonesian indigenous psychology.